Emotional Resilience, Mood States, and Emotional Stability: Foundations for Digital Emotional Analytics and Technology-Enhanced Counseling in Swamp-Region Schools - Jarkawi, Jarkawi; Sanjaya, Sanjaya; Prasiska, Emilda; Ridhani, Akhmad Rizkhi (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study examines the relationship between emotional resilience and emotional stability among high school students living in swamp ecological regions in Indonesia and evaluates the mediating role of mood states (Depression, Esteem-related Affect, Vigour). It also highlights implications for technology-enhanced student emotional monitoring. Methodology: This study employed a cross-sectional survey design with cluster sampling. Instruments included the Ecological Integrity Assessment (EIA) questionnaire, Profile of Mood States (POMS), and the Eysenck Personality Questionnaire Short Scale. Data were collected via paper-based surveys and analyzed using path analysis and SEM with maximum likelihood estimation in R and RStudio software. Main Findings: Emotional resilience was associated with lower depression and higher vigour. Mood states significantly mediated the resilience–stability relationship, with vigour showing the strongest mediating effect. Students in swamp areas demonstrated high resilience yet exhibited poorer mood conditions than national norms. Novelty/Originality of this study: Beyond psychological contributions, this study offers new insights for educational technology by identifying mood indicators that can be integrated into digital dashboards, LMS-based monitoring tools, and AI-driven counseling systems for geographically remote schools.